Empowering Women in Pioneering Oral Health Initiatives for Elderly with Hypertension - Gilang Rasuna Sabdho Wening; Ganendra Anugraha; Jihan Az' Zahra' Medina; Maulida Putri Syarifina; Mayang Aziza Hanif Ardianto; Naqiya Ayunnisa; Nathania Nurani Fripertiwi; Ni Putu Clara Pitaloka (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: An epidemiology study at Menur Public Health Center revealed that the highest case of hypertension was found in the late elderly (56-65 years) in the period of September-October 2023, most of them have dental and oral problems. Based on data, most elderly (41.82%) don’t seek any treatment when they experience toothache due to limited access and lack of individual awareness. Therefore, an empowerment program of periodic basic oral screening by cadres in Posyandu is needed for early detection to overcome possible obstacles when visiting the dentist experienced by elderly with hypertension. Objectives: To provide training for cadres in Posyandu Werda Asih regarding basic oral screening through the "Srikandi" program to improve oral health-seeking behavior for elderly with hypertension. Method: The program was conducted by providing direct training to cadres through guidebooks and posters. The program was evaluated using post-test related to basic oral screening and checklist sheet for skills. Results: After training, all cadres in Posyandu Werda Asih for the Elderly (100.00%) had a good level of understanding with an average score of 14 (the lowest score was 13 (18.18%), the highest score was 15 (18.18%)). The skills evaluation showed that all cadres (100%) were able to conduct all of the examination. Conclusion: According to post-test and checklist results, the "Srikandi" program can improve cadres' understanding and ability to perform basic oral screening. This will allow cadres to identify early dental and oral health issues and promote oral health-seeking behavior in the elderly with hypertension.